MENANAMKAN KECERDASAN SPIRITUAL ANAK USIA DINI MELALUI PENDEKATAN “NURANI” - Muhamad Parhan; Nurti Budiyanti; Kokom Siti Komariah; Mohammad Rindu Fajar Islamy; Risris Hari Nugraha (IKIP Siliwangi, 2022)
Education is the process of developing the potential God gives to each child as a subject. The reality, the potential God has not been able to develop optimally in order to strengthen the spiritual aspect of children. There needs to be an effective approach to instill spiritual intelligence in children. Child education can be considered effective if educators have good competence and are capable of developing different approaches in the learning process. Moreover, early childhood need a special approach in embedding Islamic values in accordance with the growth and development. In this study, researchers sought to formulate a “NURANI” as an accepative solution in instilling the spiritual intelligence of early childhood. The study uses a qualitative approach through analytical methods. Based on the findings and analysis in the study, the